Pathomorphological changes of bone marrow adipocytes in process of steroid-associated osteonecrosis - Sheng, Hui (e-Century Publishing Corporation, 2013)
Objective: The role of extravascular fat deposition in pathogenesis of steroid-associated osteonecrosis (ON) still remains unclear. This study aimed to explore the pathomorphological changes of bone marrow adipocytes over time in a rabbit ON model. Methods: Thirty-two adult rabbits were divided into control group (n=16) and steroid group (n=16). Rabbits in the steroid group were injected with venous lipopolysaccharide once and intramuscular methylprednisolone trice to induce ON. Rabbits in the control group were treated with normal saline of equal volume. 2 weeks (early stage; n=8) and 4 weeks (late stage; n=8) after the last steroid injection, animals were sacrificed, and bilateral femora were harvested. The density, diameter and area of bone marrow adipocytes were determined by histomorphometry, and ON was evaluated histopathologically. Results: The adipocyte density in steroid group increased by 67.1% and 54.4% at week 2 and week 4, respectively, when compared with control group, but there was no significant difference between week 2 and week 4. The adipocyte diameter in the steroid group at week 4 was significantly larger than that in the control group, but the adipocyte diameter in the steroid group at week 2 was slightly smaller than that in the control group. The adipocyte area in the steroid group increased by 44% and 83.4% at week 2 and week 4, respectively, when compared with the control group, and the adipocyte area in the steroid group at week 4 was markedly larger than that at week 2. In the control group, there were a largest number of adipocytes with 40-50 μm in diameter. When compared with the control group, most of increased adipocytes in the steroid group at week 2 were 30-40 μm in diameter, and those at week 4 were 50-60 μm in diameter. In the steroid group, histopathological examination showed ON was found in 25% (2/8) of rabbits at week 2 and 87.5% (7/8) of rabbits at week 4. Conclusion: In the process of ON, extravascular fat deposition is characterized by increased small adipocytes at the early stage and hypertrophy of adipocytes at the late stage.